The Effects of Indonesia’s Membership in BRICS on Free Trade Policies and Legal Safeguards for Domestic Enterprises - Indah Riyanti (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Indonesia's potential membership to BRICS, a coalition of prominent rising economies, presents substantial ramifications for international trade legislation and domestic regulatory structures. The research adopts a normative legal approach, employing statutory, conceptual, and comparative methodologies to examine primary legal sources, including international trade agreements, Indonesian trade regulations, and BRICS policies, alongside secondary sources such as academic articles and case studies. The principal findings indicate that Indonesia's participation in BRICS may augment its trade prospects by providing access to expansive markets and cooperative economic endeavours. Nonetheless, it presents obstacles, especially in harmonizing domestic trade regulations with BRICS' unified objectives and guaranteeing sufficient legal safeguards for local enterprises against heightened competition. The study concludes that Indonesia must strategically amend its trade legislation to reconcile international obligations with national interests, advocating for the creation of strong legal protections, enhancement of domestic enterprise capabilities, and proactive involvement in formulating BRICS trade policies to optimize advantages while minimizing risks. This paper enhances the discussion on the convergence of international trade law and domestic legal systems within the framework of growing economic alliances.